2016
DOI: 10.1590/2175-3539201502031046
|View full text |Cite
|
Sign up to set email alerts
|

Altas habilidades/superdotação: o que dizem as pesquisas sobre estas crianças invisíveis?

Abstract: ResumoEste estudo tem por objetivo analisar as teses e dissertações brasileiras, High skills / giftedness: what do the research on these invisible children say? AbstractThis study aims to analyze Brazilian theses and dissertations, from 2005 to 2014, which deal with the identification of students with high skills / giftedness. We conducted a survey with the Bank of Theses and Dissertations of the Coordination of Personal Improvement of Higher Education, the Brazilian Library of Thesis and Dissertations, the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
0
5
0
4
Order By: Relevance
“…When it comes to university students, this number is significantly lower, since giftedness in adulthood is rarely discussed in the literature. For this reason, there is an urgent need to develop works that favor the identification and monitoring of these students (Martins, Pedro, & Ogeda, 2016;Rinn & Bishop, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When it comes to university students, this number is significantly lower, since giftedness in adulthood is rarely discussed in the literature. For this reason, there is an urgent need to develop works that favor the identification and monitoring of these students (Martins, Pedro, & Ogeda, 2016;Rinn & Bishop, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to Pérez and Freitas (2014), one of the factors for this reality would be the misunderstanding on the part of educators about the real needs and difficulties encountered by these students, as well as the prejudices and myths involved regarding giftedness. In addition to these factors, there is still a great lack of knowledge about the legislation and the conduct of educational practices for the student, which contributes to the weakening of compliance with laws and resolutions (Martins, Chacon, & Almeida, 2018;Martins, Pedro, & Ogeda, 2016;Pérez & Freitas, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a survey of dissertations and theses between 2005 and 2014, Martins, Pedro and Ogeda (2016) found 91 studies on gifted students. Upon criticizing the lack of research in this field, and the lack of scientific tools to identify G/HS students, the authors emphasized that: "These gaps leave gifted students invisible within the school context, and their potential is very often unnoticed or not valued" (Martins, Pedro and Ogeda, 2016, p. 565-566).…”
Section: Introductionmentioning
confidence: 99%
“…In the identification category, the authors found 18 productions and, concerning adult intellectual giftedness, only two. Martins, Pedro and Ogeda (2016) reviewed Brazilian theses and dissertations produced between 2005 and 2014 approaching the theme of identification of people with HA/G. Results show that, out of 91 listed publications, 18 were of identification and only one had been realized in a university environment with university teachers as participants and possible indicators of students with potential for HA/G.…”
Section: Introductionmentioning
confidence: 99%